2021
DOI: 10.29262/ram.v68i4.842
|View full text |Cite
|
Sign up to set email alerts
|

Prosopis spp. en enfermedades alérgicas

Abstract: Antecedentes: Actualmente, se entiende por polinosis, a la inflamación conjuntival y/o bronquial causada por alérgenos contenidos en los granos de polen ocasionando enfermedades como la rinoconjuntivitis y asma, todo ello con muy diversos grados de severidad. La sensibilización humana a prosopis se dio a conocer ya en la década de los 1950 gracias a estudios previos realizados por Ordman Objetivos: demostrar la reactividad cutánea y la participación del polen de prosopis en los pacientes con enfermedades… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Tree pollens are the most abundant in Mexico, outnumbering weed and grass pollens [4]. Positivity to mesquite pollen in allergic patients is high (21%) [5]. In addition, mesquite pollen represents an important source of pollinosis in cities of the Sonoran Desert such as Hermosillo [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tree pollens are the most abundant in Mexico, outnumbering weed and grass pollens [4]. Positivity to mesquite pollen in allergic patients is high (21%) [5]. In addition, mesquite pollen represents an important source of pollinosis in cities of the Sonoran Desert such as Hermosillo [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies reported the immunodetection of IgE-binding proteins with molecular weights between 10 and 99 kDa in P. juliflora pollen [1]. Additionally, only two mesquite allergens (Pro j 1, Pro j 2) have been identified, characterized, and officially included in the allergen.org database by the IUIS committee [2,5,8]. However, no velvet mesquite pollen allergens have been identified so far.…”
Section: Introductionmentioning
confidence: 99%